THE IMPACT OF WORKLOAD, STRESS MANAGEMENT, AND WORK-LIFE BALANCE ON EMPLOYEE PRODUCTIVITY AT ADVENT HOSPITAL MEDAN - Dorkas Rama Widya Siregar; Toman Panggabean; Winarto (Program Studi Magister Manajemen Universitas Advent Indonesia, 2025)
This study aims to examine the impact of workload, stress management, and work-life balance on employee productivity at Rumah Sakit Advent Medan. The research employs a descriptive quantitative approach with a sample size of 81 respondents. Based on the t-test hypothesis results, it is concluded that workload has a significant impact on productivity, with a tvalue (-2.786) < ttable (1.292) and a significance value of 0.007 < 0.10. Stress management significantly influences productivity, with a tvalue (4.801) > ttable (1.292) and a significance value of 0.001 < 0.10. Additionally, work-life balance has a positive and significant effect on productivity, with a tvalue (2.520) > ttable (1.292) and a significance value of 0.014 < 0.10. The F test results indicate that workload, stress management, and work-life balance simultaneously have a significant effect on productivity, with an Fvalue (10.195) > Ftable (2.156) and a significance value of 0.001 < 0.10. Based on the coefficient of determination analysis, the adjusted R-square value is 0.256 or 25.6%, meaning that workload, stress management, and work-life balance explain 25.6% of employee productivity, while the remaining percentage is influenced by other variables or factors.